Symptomatic, biochemical and radiographic recovery in patients with COVID-19. Issue 1 (7th April 2021) - Mallia, Patrick; Meghji, Jamilah; Wong, Brandon; Kumar, Kartik; Pilkington, Victoria; Chhabra, Shaan; Russell, Ben; Chen, Jian; Srikanthan, Karthikan; Park, Mirae; Owles, Harriet; Liew, Felicity; et al.
Abstract : Background: The symptoms, radiography, biochemistry and healthcare utilisation of patients with COVID-19 following discharge from hospital have not been well described. Methods: Retrospective analysis of 401 adult patients attending a clinic following an index hospital admission or emergency department attendance with COVID-19. Regression models were used to assess the association between characteristics and persistent abnormal chest radiographs or breathlessness. Results: 75.1% of patients were symptomatic at a median of 53 days post discharge and 72 days after symptom onset and chest radiographs were abnormal in 47.4%. Symptoms and radiographic abnormalities were similar in PCR-positive and PCR-negative patients. Severity of COVID-19 was significantly associated with persistent radiographic abnormalities and breathlessness. 18.5% of patients had unscheduled healthcare visits in the 30 days post discharge. Conclusions: Patients with COVID-19 experience persistent symptoms and abnormal blood biomarkers with a gradual resolution of radiological abnormalities over time. These findings can inform patients and clinicians about expected recovery times and plan services for follow-up of patients with COVID-19.